Geochemical characteristics of Early Cambrian phosphate bearing sedimentary rocks from the Mussoorie Syncline, India: Implications for paleo-redox conditions - Saif A. Khan; Shamim A. Dar; K.F. Khan; Yasir Karim (Geosystems and Geoenvironment, 2022)
The phosphate bearing sedimentary rocks of Masrana and Kimoi blocks of Mussoorie Syncline are found to occur associated with a variety of chert-shale-carbonate with some pyrites of Tal Group of Early Cambrian age. Petro-mineralogical studies have revealed that apatite is a dominant phosphate mineral with gangue constituents as calcite, dolomite, variable amounts of quartz, pyrite, hematite as well as some organic structures. Quartz veins are also found cutting across the pellets of collophane. Major element analysis indicates that high P2O5 and CaO values designate high apatite, calcite or gypsum. The antipathetic correlation of P2O5 with most of the major oxides represents, replacement, leaching and weathering of major elements with P2O5 in the voids, cavities and veins during the formation of deposit. The results of trace elements reveal that the phosphorites are more enriched in V, Cr, Co, Ni, Cu, Zn, Ga, Rb, Sr, Y, Zr, Nb, Ba, Pb than Sc, Cs, Hf, Ta, Th, U. Higher concentration of V may be due to the presence of organic matter and its close affinity with P2O5. Vanadium (V) therefore occurs associated with Ni-Cr-Zn-Cu-Ag, which is distinctive of the organic matter obtained from the marine sediments. Rich Concentration of Ba, Cu, Ni and Zn in these phosphorites might be due to the presence of organic matter derived from marine plankton. Ni/Co ratios are low in the phosphate bearing sedimentary rocks (<5), which indicates oxic conditions. The plotted binary diagram of V/(V + Ni) versus Ni/Co also confirms oxic conditions for these samples. In the present study most of the samples have values of V/Cr below 2, whereas two samples show value above 2, indicating dominant oxic environmental conditions with mild reducing conditions. Oxic and anoxic diagenetic environment has been also supported by negative Ce and positive Eu on Post-Archean Australian Shale (PAAS) normalised REE patterns.